Exploring Ways to Enhance EFL Students' Digital Literacy in EFL Classroom - Bintang Kharisma Cristya Maharani (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2026)
As technology becomes a more integrated part of current education, digital literacy is one aspect that teachers will need to develop in their students, alongside the use of technology. Therefore, teachers, especially English as a Foreign Language (EFL) teachers, need to find practical ways to develop and enhance their students’ digital literacy ability successfully. To achieve that goal, the researcher analyzed fifteen articles published online from 2021 to 2025 using the Google Scholar database. The data results from the systematic literature review are categorized into five themes: (1) teachers design a customized reading lesson plan, (2) teachers are trained in digital literacy, (3) teachers strengthen students’ digital competencies in reading, (4) teachers raise awareness about the importance of digital literacy, (5) teachers integrate technology to students’ reading activities. The discussion of each theme is connected to the relevant literature. At the end, the study then provided suggestions for future research.